2022
DOI: 10.1002/cphc.202200211
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ion Specificity and Concentration on the Conformational Transition of Intrinsically Disordered Sheep Prion Peptide

Abstract: The structural sensitivity of the intrinsically disordered proteins with the ions has been observed experimentally; however, it is still unclear how the presence of different metal ions affects structural stability. We performed an atomistic molecular dynamics simulation of sheep prion peptide (142-167) in presence of different monovalent, divalent ions at various concentrations to find out the effect of the size, charge, and ionic concentration on the structure of the peptide. It is found that Li + ions have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 88 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…This was seen in mixed ion solutions, where some ions may preferentially occupy the area around the nucleic acid sample. Comparing this to other studies, the findings of an atomistic molecular dynamics simulation study with intrinsically disordered proteins and metal ions suggest that the stability of the protein depends on intrapeptide and peptide–water hydrogen bonds coupled with the heterogeneity of hydration water around the peptide in the presence of various ions . It is likely that similar interactions are involved with nucleic acids in ion solutions, but more experiments are needed to confirm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was seen in mixed ion solutions, where some ions may preferentially occupy the area around the nucleic acid sample. Comparing this to other studies, the findings of an atomistic molecular dynamics simulation study with intrinsically disordered proteins and metal ions suggest that the stability of the protein depends on intrapeptide and peptide–water hydrogen bonds coupled with the heterogeneity of hydration water around the peptide in the presence of various ions . It is likely that similar interactions are involved with nucleic acids in ion solutions, but more experiments are needed to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing this to other studies, the findings of an atomistic molecular dynamics simulation study with intrinsically disordered proteins and metal ions suggest that the stability of the protein depends on intrapeptide and peptide−water hydrogen bonds coupled with the heterogeneity of hydration water around the peptide in the presence of various ions. 118 It is likely that similar interactions are involved with nucleic acids in ion solutions, but more experiments are needed to confirm. A myriad of variables need to be considered when performing benchtop or computational studies involving nucleic acids and metal ions.…”
Section: T H Imentioning
confidence: 99%
“…One such good example of proteins undergoing conformational transition is the Intrinsically disordered proteins (IDPs). These proteins undergo conformational transitions due to the effect of the temperature, pH, solvents, presence of ions, and many more. IDPs/IDP regions are commonly present in all living organisms, and it is found that the amount of disorderliness increases proportionately to the complexity of the organism.…”
Section: Introductionmentioning
confidence: 99%
“…They are also linked to pathological misfolded states in those suffering from neurological disorders [ 18 , 19 , 20 ], cancer [ 18 , 21 , 22 ], cardiovascular diseases [ 18 , 23 ], or diabetes [ 24 , 25 ]. As such, the study of their interaction with solvents and ions is of crucial importance to understanding their dynamics and characterization for possible pharmacological intervention [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%